Severe neonatal manifestations of Costello syndrome. Issue 3 (26th November 2007) - Lo, I F M; Brewer, C; Shannon, N; Shorto, J; Tang, B; Black, G; Soo, M T; Ng, D K K; Lam, S T S; Kerr, B
Abstract : Background: Costello syndrome (CS) is due to mutations in HRAS, with the most common mutation being c.34G>A (p.G12S), found in most patients in all the published series. A small number of less common mutations have been reported. Population studied: HRAS mutation analysis has been undertaken in 74 predominantly British patients with a possible diagnosis of CS. A HRAS mutation was found in 27 patients, 15 of whom have been previously reported. Phenotype analysis: Four cases had an unusually severe phenotype, associated in three cases with two unusual mutations, c.35G>A, p.G12D in two cases and c.34G>T, p.G12C in the other. Hypoglycaemia, renal abnormalities, severe early cardiomyopathy, congenital lung and airway abnormalities, pleural and pericardial effusion, chylous ascites and pulmonary lymphangectasia are confirmed as part of the clinical spectrum seen in CS. A lung pathology resembling alveolar capillary dysplasia is reported in one case. Conclusion: These cases illustrate that the diagnosis of CS may be difficult in the newborn period, and should be considered in the differential diagnosis of the sick newborn infant with multisystem disease. Study of more cases will be required to establish if there is a definite association between severe disease and less common mutations.